Markers of predicting discharge from forensic psychiatric hospitals in Czechia - Sebalo, Ivan; Sebalo Vňuková, Martina; Anders, Martin; Ptáček, Radek; Páv, Marek (The International journal of social psychiatry, 2024)
BACKGROUND: Secure forensic hospital treatments are resource-intensive, aiming to rehabilitate offenders and enhance public safety. While these treatments consume significant portions of mental health budgets and show efficacy in some countries, their effectiveness in Czechia remains underexplored. Previous research has highlighted various factors influencing the likelihood of discharge from these institutions. Notably, the role of sociodemographic variables and the length of stay (LoS) in the context of forensic treatments has presented inconsistent findings across studies. METHODS: The study, part of the 'Deinstitutionalization project' in Czechia, collected data from all inpatient forensic care hospitals. A total of 793 patients (711 male, 79 female and 3 unknown) were included. Data collection spanned 6 months, with tools like HoNOS, HoNOS-Secure, MOAS, HCR-20V3 and AQoL-8D employed to assess various aspects of patient health, behaviour, risk and quality of life. RESULTS: The study revealed several determinants influencing patient discharge from forensic hospitals. Key assessment tools, such as HoNOS secure scores and the HCR-20 clinical subscale, showed that higher scores equated to lower chances of release. Furthermore, specific diagnoses like substance use disorder increased discharge odds, while a mental retardation diagnosis significantly reduced it. The type of index offense showed no influence on discharge decisions. CONCLUSION: Factors like reduced risk behaviours, absence of mental retardation diagnosis, social support and secure post-release housing plans played significant roles. The results underscored the importance of using standardized assessment tools over clinical judgement. A standout insight was the unique challenges faced by patients diagnosed with mental retardation, emphasizing a need for specialized care units or tailored programmes.
Keywords: public safety; ústavy pro duševně nemocné; Adolescent; kvalita života; Adult; Hospitals, Psychiatric; deinstitucionalizace; Patient Discharge; Male; lidé; lidé středního věku; Forensic Psychiatry; Humans; Middle Aged; propuštění pacienta; duševní poruchy; Quality of Life; legal and clinical perspectives; Young Adult; Czech Republic; Length of Stay; rehabilitation; mužské pohlaví; zločinci; Deinstitutionalization; discharge decisions; dospělí; Forensic treatment institutions; soudní psychiatrie; mladý dospělý; Česká republika; ženské pohlaví; mladiství; Mental Disorders; Criminals; Female; délka pobytu